Moderating effect of work ethics towards technology capability and logistics performance - Mohd Fathi, Abu Yaziz @ Mohamad (2019)
In today's business environment where the pace of growth has tremendously expanded, logistics has played an important role not only as supporting elements in organizations but has also influenced the performance of organizations tremendously. In relation to the logistics masterplan that has been developed by the Malaysian government, logistics performance is crucial to the support of technology capability that is facilitated with appropriate work ethics. In investigating the issues concerned, this study examined the moderating effect of work ethics on technology capability and logistics performance. Additionally, this study also investigated the importance of technology capability and logistics performance. In relation to the research objectives, proportionate stratified random sampling was used in this study as the logistics industry includes three major industries which are land and rail, airfreight, and sea freight, and to cater across the logistics industry 234 questionnaires were distributed to respondents from the Malaysian logistics organizations, and 133 usable responses, representing a 56.84% response rate, were empirically tested using the structural equation modelling by using SPSS and SmartPLS. Tests and analysis were done in relation to three main hypotheses that had been developed based on the theoretical framework. The findings justified the positive relationship between technology capability and logistics performance while, on the other hand, work ethics was found as an element that that does not affect logistics performance. The findings further revealed that work ethics do not moderate the technology capability and logistics performance relationship. On the other hand, it intensifies the necessity of work ethics to be legalized and enforced to ensure the practice of work ethics is implemented appropriately in an organization. Limitations and recommendations for future research are also discussed